2017
DOI: 10.1111/1467-9817.12098
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in children's reading comprehension across digital text types

Abstract: The present study examined children's digital text comprehension of digital text types linear digital text vs hypertext, with or without graphical navigable overviews. We investigated to what extent individual variation in children's comprehension could be explained by lexical quality (word reading efficiency and vocabulary knowledge), cognitive load factors (prior knowledge and working memory), text type and graphical overview. Participants were 93 sixth graders in a within-subject design. Word reading effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…First, prior knowledge and vocabulary knowledge are important in hypermedia learning (e.g., Boechler, Levner, Leenaars, & Steffler, ; Ford & Chen, ). They are both pivotal to reading comprehension, in linear text as well as in hypertext (Chen, Fan, & MacRedie, ; Fesel, Segers, & Verhoeven, ; Moos & Marroquin, ; Salmerón & García, ; Salmerón, Kintsch, & Kintsch, ). In a similar vein, working memory affects learning outcomes on the Internet (Pazzaglia, Toso, & Cacciamani, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, prior knowledge and vocabulary knowledge are important in hypermedia learning (e.g., Boechler, Levner, Leenaars, & Steffler, ; Ford & Chen, ). They are both pivotal to reading comprehension, in linear text as well as in hypertext (Chen, Fan, & MacRedie, ; Fesel, Segers, & Verhoeven, ; Moos & Marroquin, ; Salmerón & García, ; Salmerón, Kintsch, & Kintsch, ). In a similar vein, working memory affects learning outcomes on the Internet (Pazzaglia, Toso, & Cacciamani, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the text navigation, Klois et al found no differences in total reading time among the text designs, but fewer pages were visited in the texts containing an overview. Another study by Fesel, Segers, and Verhoeven () showed no difference in comprehension of a linear and hypertext, but the availability of an overview was beneficial in sixth graders with low prior knowledge. Level of vocabulary, but not working memory, influenced reading comprehension of digital texts.…”
Section: Introductionmentioning
confidence: 93%
“…This may have influenced the reading comprehension by enabling the students to have a holistic perception of the texts without turning the page or having to scroll through the text on the screen (e.g., Mangen et al, 2013;Rockinson-Szapkiw et al, 2013). Further, the digital text and printed text had an identical format which do not shed light on the importance of technological solutions like hypertext with or without graphical navigable overviews (Fesel, Segers & Verhoeven, 2018). At the moment, PDF is still a commonly used format of digital learning materials at the Finnish school context.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%